TINJAUAN PUSTAKA: PERANCANGAN SOLAR TRACKER OTOMATIS DENGAN INTEGRASI SISTEM PENYIRAMAN TANAMAN BERBASIS ENERGI SURYA - Sigit Maulana Malik; Dan Mugisidi (Prosiding Seminar Nasional Teknoka, 2025)
This study discusses the design of an automatic solar tracker integrated with a solar-powered plant irrigation system. The main objective is to optimize solar energy utilization while reviewing previous research on solar tracking and automatic irrigation technologies to identify the most efficient and sustainable approach. The literature review covers sensor-based tracking using LDRs, HSV image recognition methods, and microcontroller control such as Arduino. Based on the review and implementation, the system was designed to automatically adjust the solar panel’s position according to the sun’s movement, while irrigation is controlled by soil moisture sensors. Experimental results show that the integrated system improves solar energy absorption and water-use efficiency compared to conventional methods. Therefore, this integration provides an effective, energy-efficient, and eco-friendly solution suitable for small-scale agricultural applications.